A hybrid endocardial‐epicardial biventricular implantable cardioverter‐defibrillator to circumvent the tricuspid valve. Issue 2 (28th October 2020) - Ip, James E.; Krishnan, Udhay; Girardi, Leonard N.; Lerman, Bruce B.
Abstract: The development of pacing and defibrillator systems that do not involve hardware traversing the tricuspid annulus can be desirable in order to minimize lead‐related complications such as tricuspid regurgitation. Occasionally, primary tricuspid valve pathology (ie, infectious endocarditis, nonbacterial thrombotic endocarditis, and carcinoid disease) or congenital heart disease prohibits use of transvenous leads and alternative strategies are required to provide pacing or defibrillation. We describe such a case in which a biventricular implantable cardioverter defibrillator was implanted using a hybrid system involving endocardial and epicardial components.